PAIN EVALUATION AND FUNCTIONAL CAPACITY OF PEOPLE DIAGNOSED WITH KNEE OSTEOARTHROSIS THROUGH LEQUESNE ALGOFUNCTIONAL INDEX SCORES (Fiep Bulletin - online, 2014)
Osteoarthrosis is a chronic and multifactorial disease defined as an alteration in the degradation and production of cartilage, resulting in damages to the joints and adjoining tissues. The pain and the rigidity lead to a reduction in the functional capacity of the individual. Age and obesity are etiological factors closely related to the emergence of pathologies, because they change both physiological and biomechanical factors in the joints. Once the pathology is present on the knee joint, it usually brings great losses in mobility and daily live activities. This research aimed to study the relation of algical complaints and the functionalities of individuals with knee OA who went through physiotherapy treatment at the Univali's Physiotherapy Ambulatory. This is a quantitative study based on Lequesne Algofunctional Index Scores applied to patients diagnosed with knee OA at the aforementioned clinic, in which those who had refused to take part in the research were excluded along with those with a history of lower limb surgery in the previous three years. There were a total of 28 patients interviewed, whose mean age was 60 years old. Mean weigh was 78,69kg, and the BMI mean of 31,8 kg/m2. Conforming to extant literature, the subjects showed risk factors associated with the emergence and maintenance of the disease, such as: old age, obesity and of the female sex. For the most part, our sample complained about pain during rest at night, while walking and when in activities like stand up from a chair. They have also complained about morning rigidity that takes more than 15 minutes to cease. They mostly can't walk for more than one kilometer with pain, having difficulties performing daily life activities.